The Indian princes and their states - Ramusack, Barbara N. (Cambridge ; New York : Cambridge University Press, 2004)
"Although the princes of India have been caricatured as Oriental despots and British stooges, Barbara Ramusack's study argues that the British did not create the princes. On the contrary, many were consummate politicians who exercised considerable degrees of autonomy until the integration of the princely states after independence. Ramusack's synthesis has a broad temporal span, tracing the evolution of the Indian kings from their precolonial origins to their roles as clients in the British colonial system. The book breaks new ground in its integration of political and economic developments in the major princely states with the shifting relationships between the princes and the British. It represents a significant contribution, both to British imperial history in its analysis of the theory and practice of indirect rule, and to modern South Asian history, as a portrait of the princes as politicians and patrons of the arts."--Jacket
Indian princes and British imperialism -- Princely states prior to 1800 -- The British construction of indirect rule -- The theory and experience of indirect rule in colonial India -- Princes as men, women, rulers, patrons, and Oriental stereotypes -- Princely states : administrative and economic structures -- Princely states : society and politics -- Federation or integration?
"Bibliographical essay": pages 281-293
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: India -- Kings and rulers -- History; India -- History -- British occupation, 1765-1947.; India -- Politics and government -- 1765-1947.; Inde -- Histoire -- 1765-1947 (Occupation britannique); Inde -- Politique et gouvernement -- 1765-1947.; HISTORY; Kings and rulers; Politics and government; India; Maharadja's.; Kolonialisme; 1765-1947; History